In Plain Sight : Impunity and Human Rights in Thailand - Haberkorn, Tyrell (Book collections on Project MUSE., 2018)
Following a 1932 coup d'etat in Thailand that ended absolute monarchy and established a constitution, the Thai state that emerged has suppressed political dissent through detention, torture, forced reeducation, disappearances, assassinations, and massacres. In Plain Sight shows how these abuses, both hidden and occurring in public view, have become institutionalized.